The Influence of Brand Awareness and Brand Image on Customer Loyalty in Purchasing Domestic & International Flight Tickets: Case Study on Antavaya Bali - I Gede Agus Sukertha Yasa; Ni Putu Evi Wijayanti (Politeknik Pariwisata Makassar, Indonesia, 2023)
Brand awareness and brand image are essential for the business world because they can attract and make customers want to buy and use products or services owned by a company in maintaining and increasing customer loyalty. This research was conducted at Limited Company (Perseroan Terbatas/PT) of Anta Express Tour & Travel Service Branch Office Bali (Antavaya Bali), with the problems that occur, namely the price of flight tickets which are increasingly expensive during the pandemic to endemic. Still, the interest in traveling by plane is very high. This study aims to analyze the effect of brand awareness and brand image on customer loyalty at Antavaya Bali, which is analyzed using the Statistical Program for Social Science (SPSS), the type of data needed by researchers using quantitative data types. The sample used in this study was customers who purchased domestic and international flight tickets at Antavaya Bali, with questionnaires distributed to 397 respondents who were the research sample at Antavaya Bali. The sampling technique is non-probability sampling with a purposive sampling approach. The results of this study indicate that brand awareness and brand image simultaneously have a positive and significant effect on customer loyalty at Antavaya Bali.